Case study of central and local government finance in Japan - Shun-ichiro Bessho (Asian Development Bank Institute (ADBI), 2016)
This paper aims to provide an overview of the basics of Japan's local public administration and finance system and to analyze how Japan's municipalities restore their fiscal balance after a fiscal shock. In Japan, local governments play a major role in redistribution. Combined with regional disparities in tax capacities and an inflexible local tax system, there is a large vertical fiscal gap in Japan between the central and local governments - a gap that necessitates the transfer of funds from central to local governments. Under this system, the fiscal adjustments in Japan's municipalities occur mainly via changes in government investment, and they account for 63%-95% of adjustments in permanent unit innovations in grants and own-source revenue. In contrast to the role of expenditure, the municipalities' own-source revenue plays a limited role in balancing the local budget. The results of this study also reveal that 40% of the increase in own-source revenue is offset by a reduction in grants. Furthermore, municipalities can induce grants by expanding government current expenditure. Finally, this study offers and discusses some policy implications.
Keywords: H70; H72; H77; 330; Japan; local government; administrative system; local public finance; local revenue; fiscal shock; fiscal balance; tax system; "flypaper effect"